Norway : 2021 Article IV Consultation-Press Release; Staff Report; and Staff Statement. (IMF Staff Country Reports; Country Report ;, 2021)
Norway's key challenge is to get the right balance of support for recovery and adjustment until the crisis is firmly in its past. The authorities intend to continue exceptional policy support into 2021, adjusted to reflect the rebound in economic activity and pace of vaccinations in the second half of the year, and with better targeting to affected sectors. This will support the expected closing of the output gap by 2023 and help mitigate scarring, while also facilitating reallocation of capital and labor.